2013
DOI: 10.1007/s10147-013-0627-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of gemcitabine plus docetaxel in advanced or recurrent uterine leiomyosarcoma and undifferentiated endometrial sarcoma in Japan

Abstract: The gemcitabine plus docetaxel regimen without prophylactic G-CSF support was tolerable and highly efficacious in Japanese patients with advanced or recurrent LMS and UES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…3,27). Although results with GEM alone or in combination with DTX continue to be inconsistent between trials, it remains a standard second-line therapy for metastatic STS (28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…3,27). Although results with GEM alone or in combination with DTX continue to be inconsistent between trials, it remains a standard second-line therapy for metastatic STS (28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this may be that our study included fewer patients with leiomyosarcoma, particularly of the uterus (n = 1), or undifferentiated pleomorphic sarcoma (n = 3), which might have a higher sensitivity to GD as shown in previous studies [11, 12, 19, 20]. In a phase II study reported by Pautier et al [19], RR was 24% in uterine leiomyosarcoma, but only 5% in other leiomyosarcomas.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, in a more recent French randomized phase II study, the RR was higher for leiomyosarcoma of uterus than for leiomyosarcoma of other organs (24% vs. 5%) [19]. A small Japanese phase II study reported that a response was observed in three of eight (38%) patients with uterine leiomyosarcoma [20]. Despite the lack of phase III studies, these phase II studies suggest that GD is a promising regimen in soft-tissue sarcoma, possibly particularly in uterine leiomyosarcoma, at least as second- or later-line therapy.…”
Section: Introductionmentioning
confidence: 95%
“…Combination therapy of gemcitabine and docetaxel has been a standard regimen of chemotherapy according to results of phase II trials [15][16][17], and there have been favorable results from a phase II trial (SARC 005) regarding adjuvant treatment with docetaxel and gemcitabine followed by doxorubicin in patients with uterus-limited ULMS [18]. However, our previous report revealed that dose reduction due to bone marrow suppression was frequently required with docetaxel and gemcitabine therapy, especially in Japanese patients [19]. According to the results of previous studies, clinical features of ULMS were although FIGO stage was distributed early stage, but exhibited a poor prognosis (Table 3).…”
Section: Discussionmentioning
confidence: 94%